System innovation and the transition to sustainability theory, evidence and policy - Elzen, Boelie, 1953-; Geels, Frank W., 1971-; Green, Kenneth; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2004)
This book considers two main questions: how do system innovations or transitions come about and how can they be influenced by different actors, in particular by governments. The authors identify the theories which can be used to conceptualise the dynamics of system innovations and discuss the weaknesses in these theories. They also look at the lessons which can be learned from historical examples of transitions, and highlight the instruments and policy tools which can be used to stimulate future system innovations towards sustainability. The expert contributors address these questions using insights from a variety of different disciplines including innovation studies, evolutionary economics, the sociology of technology, environmental analysis and governance studies. The book concludes with an extensive summary of the results and practical suggestions for future research.
pt. 1. Theoretical explorations of transitions -- pt. 2. Empirical examples of transitions -- pt. 3. Transition policy -- pt. 4. Tools for transition policy and empirical illustrations.
Includes bibliographical references and index.
Keywords: Sustainable development; Environmental policy; System theory; Electronic books